The Water We Eat (Combining Virtual Water and Water Footprints) - Antonelli, Marta (Springer, 2015)
The translation of the book was sponsored by Carlo Mazzola, President of Fondazione Eureka. Fondazione Eureka was established in 2014 and is based in Milan; its objective is to develop and propose models of sustainable consumption of resources to reduce the impact that daily consumption habits have on the planet and, therefore, in our lives. The Foundation develops research projects in partnership with prestigious Italian universities and research centers for rigorous and scientific analysis as well as numerical quantifications of environmental, economic, and social impacts of the consumption of resources, such as water. The activities of the Foundation are addressed to the general public by providing user-friendly software applications to promote consciousness of citizens and to networks and study groups for the distribution of researches and the sharing of effective solutions.